Pendidikan Pola Hidup Sehat Pada Lansia Menggunakan Media Video Di Panti Sosial Harapan Kita - Clara Mei Sintya; Azizah Husin; Yanti Karmila Nengsih (Universitas Dehasen Bengkulu, 2023)
Knowledge and attitudes are very influential on behavior change. The elderly need education that aims to foster awareness including aspects of knowledge, attitudes and actions so as to realize changes in correct healthy behavior, because some elderly are still lacking in implementing a healthy lifestyle properly. The purpose of this study is as an education for the elderly about healthy lifestyles using video media at UPTD Harapan Kita Elderly Social Institution, South Sumatra Province. This study used the Experiment method with a pre-experimental research design of one group pretest-posttest. The virginity retrieval technique uses questionnaires and percentage descriptive data analysis techniques. The subjects in this study used purposive sampling with a total of 31 elderly people. The results showed that healthy lifestyle education for the elderly using video media in its delivery increased from 35% to 87%. This shows that indeed video media can improve learning outcomes because with video media, the elderly will better understand the material delivered by educators through the learning videos played. A healthy way of life must be done consistently and promptly, so that a solid way of life is a person's way of life to reduce disease.